2020
DOI: 10.3390/en13040995
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Effectiveness of Sulfate-Reducing Bacteria Combined with Coal Gangue in Repairing Acid Mine Drainage Containing Fe and Mn

Abstract: In view of the characteristics of the high content of SO42−, Fe2+ and Mn2+ in acid mine drainage (AMD) and low pH value, based on adsorption and biological methods, coal gangue was combined with sulfate-reducing bacteria (SRB). On this basis, four dynamic columns, including Column 1 (SRB combined with spontaneous combustion gangue from the Gaode coal mine), Column 2 (SRB combined with spontaneous combustion gangue from Haizhou), Column 3 (SRB combined with gangue from Haizhou), and Column 4 (SRB combined with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 49 publications
2
12
0
Order By: Relevance
“…It can be seen from ORP and COD that SRB in column 1 # had almost no activity due to the support of no carbon source. Therefore, the slow increase of pH mainly depended on lignite, indicating that lignite has the ability to regulate pH, which is consistent with the results of Dong 31 . Lignite can release alkalinity to combine with H + in solution to raise pH.…”
Section: Resultssupporting
confidence: 89%
“…It can be seen from ORP and COD that SRB in column 1 # had almost no activity due to the support of no carbon source. Therefore, the slow increase of pH mainly depended on lignite, indicating that lignite has the ability to regulate pH, which is consistent with the results of Dong 31 . Lignite can release alkalinity to combine with H + in solution to raise pH.…”
Section: Resultssupporting
confidence: 89%
“…Coal gangue (CG), a residue with lower carbon content than coal discharged during mining, washing, and the processing of coal tunneling, accounts for ∼10%–15% of unprocessed coal harvest 1–3 . Owing to the rapid growth of the coal mining industry, the total amount of CG is rising sharply and gradually becoming one of the most significant industrial solid residues; global CG production was about 0.7–1.5 billion tons in 2020 4 .…”
Section: Introductionmentioning
confidence: 99%
“…Coal gangue (CG), a residue with lower carbon content than coal discharged during mining, washing, and the processing of coal tunneling, accounts for ∼10%-15% of unprocessed coal harvest. [1][2][3] Owing to the rapid growth of the coal mining industry, the total amount of CG is rising sharply and gradually becoming one of the most significant industrial solid residues; global CG production was about 0.7-1.5 billion tons in 2020. 4 According to the Guizhou Energy Administration, owing to the rapid expansion of coal production capacity, the quality of raw coal in China has decreased, and the ash content has increased since 2016.…”
Section: Introductionmentioning
confidence: 99%
“…In a study by Luptakova et al, a mixed SRB culture of Desulfovibrio and Desulfotomaculum effectively removed Cu 2+ from model solutions after 5–6 days using one batch reactor [ 153 ]. Dong et al showed that SRB combined with coal gangue achieved high treatment efficiency in repairing AMD, i.e., it achieved the highest removal percentages of chemical oxygen, SO 4 2− , Fe 2+ , and Mn 2+ [ 154 ]. SRB isolated by Ma et al [ 155 ] from loess polluted by coal AMD exhibited almost 100% immobilization of Fe 2+ , Cd 2+ , and Zn 2+ by hydrogen sulfide precipitation after 18 days.…”
Section: Bioremediation Of Contaminated Sites By Native Microorganismsmentioning
confidence: 99%